The effects of female sexual steroids on gastric function and barrier resistance of gastrointestinal tract following traumatic brain injury - Zakieh Keshavarzi; Mohammad Khaksari (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim was to assess the alteration of gastric function and barrier function of gastrointestinal (GI) tract following diffuse brain injury in varying ovarian hormone status. Materials and Methods: Diffuse traumatic brain injury (TBI) was induced by Marmarou method. Rats were randomly assigned into 10 groups: Intact, sham + ovariectomized female (OVX), TBI, TBI + OVX, vehicle, estradiol (E2), progesterone (P), E2 + P, estrogen receptor alpha agonist and estrogen receptor beta agonist (DPN). Endotoxin levels were measured using enzyme-linked immunosorbent assay method. All the parameters were measured 5 days after TBI. Results: Intragastric pressure was significantly decreased in TBI as compared to the intact group (P < 0.001) and this was lower in TBI group versus TBI + OVX group (P < 0.05). Pretreatment with steroid hormones and their agonists did not have any effect on the gastric pressure compared to TBI + OVX or vehicle groups. Inflammation, congestion, ulcer and erosion were seen in the TBI rats. All treatment groups worsen the tissue condition so that the presence of thrombosis also was seen. The trauma induction did not have any effect on the serum and intestinal endotoxin levels. DPN had caused a significant reduction in serum levels of endotoxin compared with OVX + TBI group (P < 0.05). Conclusion: Pretreatment with sexual steroids is not useful in the treatment of GI dysfunction induced by TBI. The treatment with all sexual female hormones worsens the gastric tissue condition. Furthermore, the applied weight was not enough for releasing of endotoxin. It seems that estrogen reduced the endotoxin levels by estrogen beta receptor.